The predictors of Māori electoral roll choice and knowledge: rangatahi Māori voter enrolment in a representative New Zealand youth survey - Greaves, Lara M.; Hayward, Janine; Barnett, Daniel; Crengle, Sue; Clark, Terryann C. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2023)
Every five years and when initially enrolling to vote, Māori have the choice between the Māori roll or the general roll. Research has explored the predictors of roll choice for older adults, but this paper presents the first exploration of roll choice for rangatahi Māori (Māori youth; aged 13–18), and the predictors of rangatahi not understanding the difference between rolls. We draw on Māori data (n = 1528) from Youth19 which surveyed students from a random sample of schools from Tai Tokerau, Tāmaki Makaurau, and Waikato. We find those Māori who also identify as Pākehā (New Zealand European) are less likely to opt for the Māori roll, but those who know their Iwi, are comfortable in Māori social surroundings, feel a spiritual connection to land and the presence of their ancestors in their lives, or feel the drive to be respected as Indigenous, are more likely to choose the Māori roll. Older rangatahi are more likely to say they understand the question, as are those with study plans post-secondary school, and who say they are comfortable in Māori social settings. These results contribute to a body of knowledge valuable for those seeking to increase voter enrolment and enrolment on the Māori roll.Glossary of Māori words: Hapū: kinship group, generally smaller than Iwi; sometimes translated to sub-tribe; hui: meeting; Iwi: broader tribal unit or grouping; nation; kaitiaki: guardian, steward, trustee; kanohi-ki-te-kanohi: face to face/in person; kapa haka: Māori performing arts; traditional performance; Kura Kaupapa Māori: Māori language/Māori medium schools; mana whenua: Māori group(s) who have authority, power, or rights over a certain area of land; marae: meeting house and the area surrounding it; mātauranga Māori: Māori ways of knowing/knowledge; Pākehā: New Zealanders of European descent; rangatahi: youth; rohe: area, region; tangata whenua: Indigenous peoples of Aotearoa New Zealand; people(s) of the land; te reo Māori: the Māori language; te Tiriti o Waitangi: the Māori language version of the Treaty of Waitangi; tīpuna/tupuna: ancestors; waka ama: canoe sport; wānanga: meetings for discussion, deliberation, forums; whanau: family, extended family, or family-like group; whanaungatanga relationship, kinship, sense of family-like connections between people.
Keywords: māori roll; political participation; rangatahi; tūpuna; voter enrolment; voting

The Māori Electoral Option: How can trends in roll choices be explained? - Bargh, Maria (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
The Mäori Electoral Option is a period of 4 months, every 5 years, when Mäori electors can choose whether to be on the Mäori or the General Electoral Roll. The outcome of the Mäori Electoral Option is a key factor in determining the number of Mäori seats in the New Zealand Parliament. The Electoral Commission estimates that approximately 6,000 Mäori voters each year request to change electoral roll, but in 2017 over 19,000 voters applied to change. Why were so many more Mäori wanting to change and why did they not know they could only change during the Mäori Electoral Option held every 5 years? The following year, the 2018 Mäori Electoral Option saw the first net increase of Mäori changing to the general roll since 1996. This article uses data gathered from the results of Mäori Electoral Options 1991–2018, an anonymous survey, and evaluations of Mäori Electoral Option campaigns to consider how the shifting trends in roll choices might be explained.
Keywords: elections; kāwanatanga; māori electorates; māori seats; voting

Challenges on the path to Treaty-based Local Government relationships - Bargh, Maria (Kōtuitui: New Zealand Journal of Social Sciences Online, 2021)
In this article I examine some of the challenges for Māori and Local Government on the path to Treaty-based Local Government relationships. I suggest significant challenges exist in three core areas. The first relates to the attitudes towards the ideas of Treaty-based Local Government and evident in common terminology which has a narrow focus on the identity of Māori as ‘representatives' rather than ‘Treaty partners’. The second area of challenge is in having Māori wards/constituencies established which, when they are established, are symbolically the beginnings of an acknowledgment of Treaty obligations and relationships. The third challenge is the lack of good data which limits understandings of Māori involvement in Local Government. In the second part of the article I ask whether any specific challenges can be seen that might impact on Treaty-based relationships in regard to Māori involvement as candidates and voters in Local Government elections.
Keywords: elections; local elections; local government; māori electorates; tiriti o waitangi/treaty of waitangi; treaty obligations; treaty-based relationships; voting